Evaluation of N-(2-Thienylidene)amines, N-(2-Hydroxybenzylidene)amines and 3-Iminoindolin-2-ones as Antileishmanial Agents - M.S.A. Al-Kahraman, Yasser; S. Singh, Girija; Yasinzai, Masoom (Letters in Drug Design & Discovery, 2011)
The paper describes the synthesis and antileishmanial activity of N-substituted imines, obtained from the reactions of primary amines with three biologically important aldehydes/ketones, thiophene-2-carbaldehyde, 2- hydroxybenzaldehyde (salicylaldehyde) and indoline-2,3-dione. Of the fourteen compounds screened from three classes, five compounds showed significant antileishmanial activity. Among the three classes of imines, the class of N-(2- thienylidene)amines showed much better activity than the other two classes. N-(2-Thienylidene)benzhydrylamine showed IC50 value of 0.51 μg/ml. The effect of substituents on the bioactivity is discussed.
Keywords: Salicylaldehyde